Work readiness among vocational high school students: Learning agility and perceived social support - Zakira Adila Jari; Satwika, Pratista Arya (HUMANITAS published by Universitas Ahmad Dahlan., 2025)
In Indonesia, the highest percentage of the Open Unemployment Rate (TPT) comes from graduates of Vocational High Schools (SMK), reaching 9.01%. One of the main causes is the lack of work readiness. To address this issue, exploring factors that can contribute to improving students' readiness to enter the workforce is crucial. Therefore, this study investigated the role of learning agility and perceived social support in work readiness among Vocational High School students. The participants were 93 grade XI students majoring in office management of vocational high school in Surakarta selected using simple random sampling technique. The scales used were the Work Readiness Scale (α = 0.95), the Learning Agility Scale (α = 0.92), and the Multidimensional Scale of Perceived Social Support (α = 0.92). Data were analysed using the Multiple Regression Model. The results showed that learning agility can partially predict students' work readiness, but perceived social support does not significantly predict students' work readiness. Meanwhile, combined, learning agility and perceived social support contribute 33.7% to work readiness. These findings suggest a need for schools to design learning programs that not only focus on technical skills but also train students to become resilient, flexible, and adaptive learners.